2014
DOI: 10.5194/hess-18-4311-2014
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the connections of ENSO and the rainfall regime of East Africa and the upper Blue Nile region using a climate model of the Tropics

Abstract: Abstract. We simulate the observed statistical relationship between ENSO and the rainfall regime of the upper Blue Nile using the tropical-band version of the regional climate model RegCM4 (or Reg-TB). An ensemble of nine simulations for the 28-year period 1982-2009 is completed to investigate the role of ENSO in modulating rainfall over the upper Blue Nile catchment. Reg-TB shows a good skill in simulating the climatology of temperature, outgoing long-wave radiation patterns as well as related atmospheric cir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…This is the same ENSO-streamflow relationship found in Eltahir [55] and Dettinger and Diaz [8], and may result from integrating less significant but anomalous precipitation from upstream reaches through hydrological processes (e.g. evapotranspiration, infiltration, and discharge) over large catchment areas [56,57]. Additionally, in the upstream regions of the Nile river, anomalous soil moisture conditions affect the corresponding streamflow patterns more than precipitation in DJF (figures 3(e)-(g), DJF).…”
Section: Africasupporting
confidence: 61%
“…This is the same ENSO-streamflow relationship found in Eltahir [55] and Dettinger and Diaz [8], and may result from integrating less significant but anomalous precipitation from upstream reaches through hydrological processes (e.g. evapotranspiration, infiltration, and discharge) over large catchment areas [56,57]. Additionally, in the upstream regions of the Nile river, anomalous soil moisture conditions affect the corresponding streamflow patterns more than precipitation in DJF (figures 3(e)-(g), DJF).…”
Section: Africasupporting
confidence: 61%
“…The data range covered 65 years of summer rainfall (1951-2015) and 50 years of spring rains (1951-2000) over Ethiopia. There are some previous studies [52][53][54] that also showed the availability of using CRU data.…”
Section: Rainfall Datamentioning
confidence: 99%
“…The teleconnections known to act over East Africa are IOD [Saji et al, 1999] and ENSO [Ropelewski and Halpert, 1987;Trenberth, 1997]. In particular, most of the interannual variability during the short rains as well as other seasons has been linked to IOD [Behera et al, 2005;Black et al, 2003;Conway et al, 2007;Lanckriet et al, 2015;Marchant et al, 2007;Omondi et al, 2013;Williams and Funk, 2011;Zaroug et al, 2014]. Several studies have also found the imprint of ENSO on the variability of the short rains over parts of East Africa [Giannini et al, 2008;Indeje et al, 2001;Plisnier et al, 2000;Schreck and Semazzi, 2004;Segele et al, 2009;Smith and Semazzi, 2014;Sun et al, 1999].…”
Section: Introductionmentioning
confidence: 99%